New varieties of vine rules in relation to the European Union the requirements compared by biochemical - Eugeniu Alexandrov (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The process of obtaining distant hybrids, as well as any crossing of cultivars of V.vinifera L. with representatives of species possessing the necessary qualities (resistance to diseases and pests, low temperature, etc.) may change the spectrum of chemical and biochemical compounds responsible for flavour, colour and taste of grapes, obtained juice and wine. Botanical description of distant hybrids was performed during all phases of the vegetative stages; the organs of the plants were studied from spring, at bud unfolding, until early autumn, at the fall of the leaves. For the determination of diglucoside-3,5-malvidin, the fluorimetric method, for determining the methyl anthranilate, the gas chromatographic method was applied. Based on the analyzes of biochemical constituents of grapes of the distant hybrids: DRX-M4-578; -502; -571; -660; -609; -580; etc., compared to the traditional cultivars "Feteasca albæa", "Neteasca neagra", "Raræa neagræa" and "Negru de Ialoveni", it has been found that these varieties are similar. So, the distant hybrids of grapevine haven't inherited unwanted characters for vines, some of them are strictly limited (diglucoside-3,5-malvidol). These hybrids don't have the specific characteristics of direct production hybrids, characterised by the foxat taste of the grape berries, caused by the presence of the methyl anthranilate. The distant hybrids studied according to the classical uvologic and technological principles can be classified as follows: distant hybrids are attributed to the table vine species (DRX-M4-502; DRX-M4-512 etc.) and distant hybrids have mixed properties (DRX-M3-3-1; DRXM4-580; DRX-M4-640 etc). According to the physical and biochemical indices of the grapes of the studied distant hybrids, their characteristics are similar to European vine species.
Keywords: 330; berry; diglucozide-3; 5-malvidol; methl anthranilate; hybrids; resistence